Hubungan Pola Asuh Orang Tua dengan Kenakalan Remaja pada Peserta Didik Program Paket C Sanggar Kegiatan Belajar Surabaya - Permatasari, Intan; Mardliyah, Sjafiatul (J+PLUS UNESA, 2024)
This research discusses the relationship between parenting patterns and juvenile delinquency in Package C students at the Surabaya Learning Activity Studio. Deviant behavior itself is something that can cause many problems. The aim of this research is to link parenting patterns with juvenile delinquency among students at SKBN Surabaya. This study uses a quantitative approach . The data collection techniques used in this research were questionnaires and documentation. Techniques for analyzing data are validity tests, reliability tests, normality tests, linearity tests, and hypothesis tests using product moment. The results of this study indicate that there is a significant relationship between parenting styles and juvenile delinquency. The result of calculating this data is that the r calculation produces a result of 0.521 and the t calculation is 4.4897, so from these results it can be concluded that Ha is accepted and Ho is rejected and there is a relationship between parenting style and juvenile delinquency in the SKB Surabaya Package C Program.